Progress on Polymer Composites With Low Dielectric Constant and Low Dielectric Loss for High-Frequency Signal Transmission - Wang, Lu; Yang, Jing; Cheng, Wenhua; Zou, Jiajia; Zhao, Dan (Frontiers in Materials, 2021)
The development of information transmission technology towards high-frequency microwaves and highly integrated and multi-functional electronic devices has been the mainstream direction of the current communication technology. During signal transmission, resistance-capacitance time delay, crosstalk, energy consumption increase and impedance mismatch restrict the high density and miniaturization of Printed circuit board (PCB). In order to achieve high fidelity and low delay characteristics of high-frequency signal transmission, the development of interlayer dielectric materials with low dielectric constant (Dk) and low dielectric loss factor (Df) has become the focus of researchers. This review introduces the dielectric loss mechanism of polymer composites and the resin matrix commonly used in several high-frequency copper-clad laminates, and mainly describes how to reduce the dielectric constant and dielectric loss of materials from the level of molecular structure design, as well as the effect of fillers on the dielectric properties of polymer substrates. As a kind of potential functional fillers for dielectric polymeric composites, the carbon nanofillers are used to tailor the dielectric properties of their composites via different dimensions and loadings, as well as their proper preparation methods. This review finally summarizes the interface bonding failure mechanism and a feasible idea to optimize the dielectric properties of polymer matrix composites is also proposed.